(De)globalization, complexity and uncertainty: towards ambidextrous business management (GEON Journal (Management, Organizations and Business), 2024)
Problematic: The subprime crisis, alongside impacts such as COVID -19 and the conflict in Ukraine have brought to light the risks associated with economic globalization built upon complex but vulnerable supply networks. These events, together with other criticisms, have also led companies to consider the need to move towards a certain degree of deglobalization. However, will this potential de-globalized world, characterized by less interconnectedness and some fragmentation, be inherently less complex and uncertain? How should business management deal with it? Objectives: This study aims to achieve two objectives: firstly, to analyze criticisms of the globalization process and potential responses in the form of deglobalization; secondly, to highlight management developments enabling companies to face the future environment. Materials and methods: Adopting a primarily complexity-based approach, this analysis delves into literature regarding globalization and recent trends in deglobalization, as well as the latest contributions in business management addressing complexity and uncertainty. Results: The trajectory towards a certain degree of deglobalization appears to be established, although the future world will continue to be complex and uncertain, requiring adaptive business management. Discussion: Business management, particularly in the long term, will necessitate substantial changes, primarily rooted in ambidexterity. Conclusions: In the medium term, business action should focus on restructuring supply networks, digitalization and attention to people. Long-term objectives revolve around sustainability and innovation, achievable through the development of several interrelated capabilities, with emphasis on six ambidextrous traits. Contribution/originality: This work contributes to the analysis of the future organizational environment through a complexity-based perspective and advances the innovative proposition of several ambidextrous traits that companies should develop to survive in the near future.
Keywords: ambidexterity; complexity; deglobalization; business management; globalization; uncertainty